The association of perceived ethnic discrimination and institutional verbal violence with chronic stress in an immigrant sample: The role of protective factors - results from the VIOLIN study - Hauck, Felicitas; Borho, Andrea; Romero Gibu, Lucia; Atal, Mojib Rahman; Dederer, Sevil; Bendel, Petra; Morawa, Eva; Erim, Yesim; Jansen, Silke; Rohleder, Nicolas (Journal of Migration and Health, 2024)
Immigrants are exposed to a variety of stressors, such as ethnic discrimination, and therefore experience a higher risk of developing adverse health outcomes. However, the role of potentially protective psychological factors is not well-studied. The present study addresses the question how discrimination and institutional verbal violence (IVV)1 are associated with chronic stress in an immigrant sample. In addition, this study highlights moderating effects of migration-specific variables (first or second migration generation and citizenship status). Participants (n = 232; 69.4 % female) completed an online-survey, which included demographics, questionnaires (Everyday Discrimination Scale, EDS; Perceived Stress Scale, PSS-4; Resilience Scale, RS-11; Self- Compassion Scale, SCS-SF) as well as a self-developed questionnaire on institutional verbal violence. Only participants living in Germany with migration background (self or one parent migrated to Germany) were included. Results showed that perceived discrimination and institutional verbal violence were highly associated with chronic stress. Further, self-compassion buffered the connection between discrimination and stress, whereas resilience was no protective factor. The inclusion of migration-specific variables showed that the secondgeneration sub-group experienced less discrimination-related stress and self-compassion was shown to be particularly protective within this sub-group. Citizenship status did not appear to be a moderator, but especially persons with temporary or permanent residence status, compared to German/EU-citizens, reported higher values of verbal violence and discrimination-related stress. These findings highlight the importance of considering not only psychological but also structural and societal protective and risk factors, as they may be differentially associated with immigrants’ stress perceptions. Implications for future research and practical implementations are presented.<br
Keywords: Ethnic discrimination Verbal violence Chronic stress Self-compassion Migration generation Citizenship status